Students’ Responses on the Application of Authentic Assessment in EFL Reading Class - Triubaida Maya Ardianti; Lutfi Ashar Mauludin (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2017)
Reading offers a combination of challenges for EFL students. In this case, they meet layered difficulties from language barriers to lack of exposure to critically interpret the reading materials. Being aware of this circumstance, the present study attempts to examine the students’ responses in an EFL reading class where authentic assessment is being implemented to help them learn to read in English. In particular, this study is conducted to discover the students’ responses if the instructional framework could accommodate their needs in learning to read in L2. Further, a qualitative case study is applied, and data are collected from questionnaire and 16 meeting field-observation. Results of the study indicate that the students gradually respond positively to the application of authentic assessment. They reveal that authentic assessment (1) motivates them have a reading routine, so that they can find a lot more vocabulary and get used to English discourse, (2) trains them to demonstrate their reading comprehension in more constructive ways such as writing reviews, presentations, and discussions, and (3) helps them assess their own reading performance. In sum, the students admit that authentic assessment helps most of thethem enjoy reading throughout a series of social practices, in this case, the application of authentic assessment components including portfolios, performance assessment, and self-assessment.Keywords: students’ responses, authentic assessment, EFL reading